Theorizing in Information Systems Research Using Focus Groups - Belanger, France (Australasian Journal of Information Systems, 2012)
Information Systems researchers have embraced a number of qualitative research approaches and methodologies, including interviews, observations, and even action research. One approach gaining visibility in IS research is the focus group method. Focus groups have the potential to provide great insights into phenomena of interest to IS researchers as they allow researchers to get deeper into the topic of interest by providing more background information about the circumstances of the subject’s answers or opinions. This paper offers a discussion of the focus group research approach and a review of focus group research in the information systems literature, and recommendations for the use of focus groups in IS theorizing. The discussion highlights the idea that focus group research is particularly useful for exploratory research on topics where concepts normally emerge through interactions among individuals or where concepts are initially unclear to participants, and as part of a multi-method research program for theory development. We provide examples of focus groups used in theory development and discuss limitations of the approach.